2018
DOI: 10.1038/s41591-018-0125-4
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin inhibits gluconeogenesis via a redox-dependent mechanism in vivo

Abstract: Metformin, the universal first-line treatment for type 2 diabetes, exerts its therapeutic glucose-lowering effects by inhibiting hepatic gluconeogenesis. However, the primary molecular mechanism of this biguanide remains unclear, though it has been suggested to act, at least partially, by mitochondrial complex I inhibition. Here we show that clinically relevant concentrations of plasma metformin achieved by acute intravenous, acute intraportal or chronic oral administration in awake normal and diabetic rats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
194
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(221 citation statements)
references
References 70 publications
12
194
3
4
Order By: Relevance
“…Finally, it was shown that low concentrations of metformin (≤2 nmol/mg of protein), which does not inhibit complex I, may attenuate gluconeogenesis by a redox-independent mechanism-allosteric regulation of phosphofructokinase-1 (PFK1) and/or fructose bisphosphatase-1 (FBP-1). 13 This study is also in direct disagreement with observations of Madiraju et al, 17,37 which proposed redox dependent mechanism and ascribed the shift in NADH/NAD + ratio to inhibition of mGPDH (see above).…”
Section: Allosteric Regulation Of Pfk1 and Fbp-1contrasting
confidence: 68%
See 2 more Smart Citations
“…Finally, it was shown that low concentrations of metformin (≤2 nmol/mg of protein), which does not inhibit complex I, may attenuate gluconeogenesis by a redox-independent mechanism-allosteric regulation of phosphofructokinase-1 (PFK1) and/or fructose bisphosphatase-1 (FBP-1). 13 This study is also in direct disagreement with observations of Madiraju et al, 17,37 which proposed redox dependent mechanism and ascribed the shift in NADH/NAD + ratio to inhibition of mGPDH (see above).…”
Section: Allosteric Regulation Of Pfk1 and Fbp-1contrasting
confidence: 68%
“…They subsequently associated decreased hepatic gluconeogenesis upon metformin treatment with modulation of redox state through GPS inhibition. 17,37 In their experiments on rats, metformin dosing achieved similar plasma concentrations to that of metformin-treated patients. During both acute (30 minutes, 20-50 mg/kg intravenously) and chronic (30 days, 50 mg kg −1 day −1 intraperitoneally) treatment, they observed increased levels of plasma lactate and glycerol, lower levels of fasting glucose and endogenous glucose production.…”
Section: Mitochondrial Glycerophosphate Dehydrogenasementioning
confidence: 96%
See 1 more Smart Citation
“…The inhibition of gluconeogenesis was attributed to either the decrease in the cell ATP/ADP ratio (9,10,14) or to activation of AMPK 3 resulting from the raised AMP (15). Subsequently, arguments were proposed in support of AMPK-independent mechanisms through either lowering of ATP or raised AMP (16) causing inhibition of glucagon signaling (17) or FBP1 (18) or alternatively through inhibition of mitochondrial glycerophosphate dehydrogenase (mGPDH) (19,20). Cellular studies using high millimolar metformin concentrations and showing substantial lowering of gluconeogenesis and cell ATP are now thought to be of limited relevance, because in diabetes therapy, blood metformin concentrations are in the low micromolar range, and substantial lowering of ATP is thought not to occur during metformin therapy (1,6).…”
mentioning
confidence: 99%
“…One proposes mild elevation in AMP through compromised hepatic energy status, resulting in inhibition of glucagon signaling (17) and allosteric inhibition of FBP1 (18). The other proposes inhibition by metformin of mGPDH, the key enzyme of the GP-shuttle, which is one of two shuttles that transfers reducing equivalents from the cytoplasm to the mitochondria (19,20). mGPDH is a flavinlinked mitochondrial dehydrogenase that catalyzes G3P oxidation to dihydroxyacetone-P on the cytoplasmic side coupled to the reduction of FAD and transfer of electrons to the respira-tory chain via ubiquinone (21).…”
mentioning
confidence: 99%